Synthesis and characterization of ZnO particles and MWNTs-ZnO nanocomposites - Latip, Suzanita (2012)
Multi-walled carbon nanotubes (MWNTs) were functionalized using various acid treatments to introduce functional groups, especially carboxylic acid groups on the surface of MWNTs. Different acid solutions namely nitric acid, citric acid, chromic acid and mixture of nitric and sulphuric acid were used for this purpose. There are different parameters that had been used for the synthesis MWNTs-ZnO nanocomposites, including different acid treatments, the ratios between MWNTs and zinc precursor and surface adsorption of anionic and cationic surfactants. Each parameter was explored to investigate the effect on the physio-chemical properties of the MWNTs-ZnO nanocomposites prepared by simple, co-precipitation methods. Through various acid treated of MWNTs, ZnO nanoparticles were selectively attached to the nanotubes and the presence of functional groups were further confirmed. MWNTs-ZnO nanocomposites that were prepared by pre-treatment of MWNTs with different acids gave dispersion of ZnO nanoparticles attached on the MWNTs but it was not formed uniformly on the surface of the MWNTs. Each of MWNTs-ZnO nanocomposites prepared by pre-treatment of MWNTs with different acids gave different morphologies such as thin flake ZnO nanoparticles shown by FESEM study. On the other hand, different ratios between MWNTs and zinc precursors gave ZnO nanoparticles time to formed different shapes on the surfaces of MWNTs such flower-like shape. By verifying the ratios of MWNTs and the precursors, the newly formed of ZnO nanoparticles morphologies such as flower-like ZnO nanoparticles attached on the MWNTs lead to new properties of MWNTs-ZnO nanocomposites. The ratio of 1:0.5 between MWNTs to Zn leads to better dispersion in the formation of ZnO on the surface of MWNTs. The increase in the ratios of MWNTs to ZnO leads the agglomeration of ZnO nanoparticles and increased the size of ZnO. The morphologies of ZnO nanoparticles showed non-uniform, long finger-like irregular granular structure and rod-like structure when it was synthesized by coprecipitation method, with the addition of CTAB and SDS, respectively. The surface adsorption of Sodium dodecyl sulphate (SDS) and cetyltrimethylammonium bromide (CTAB) enable the decoration of MWNTs with a uniform size of zinc nanoparticles. MWNTs-ZnO nanocomposites prepared with addition of surfactants gives better distribution of ZnO nanoparticles formation on the surface of MWNTs and decreased their particle size to 15 nm. The main problem in this research is the agglomeration of ZnO nanoparticles. They were agglomerated on the surface of MWNTs and makes the potential properties of the nanocomposites cannot fully discover. The inertness of MWNTs were also a challenge, but it has overcome with vary the type acid used. The use of green beans as biotemplating agent showed that, ZnO nanoparticles can be formed with desired morphology and dimension. The result indicates that several surface morphology can be formed by adjusting the concentration of precursor solution. The average diameter of the particles was less than 1 m. The green beans are thought to be responsible to control the size and morphology of the resulting ZnO nanoparticles by biotemplating process.